Remote Sensing Monitoring and Variation Analysis of Ungauged Tributary Discharge in Three Gorges Reservoir Area - LOU He-zhen, ZHOU Bai-chi, SONG Wen-long, FENG Tian-shi, YANG Sheng-tian, MENG Juan, GUI Rong-jie, LIU Hong-jie (长江科学院院报)
The Three Gorges Reservoir (TGR) area features a large number of tributaries, but the lack of basic hydrological station monitoring leads to the scarcity of hydrological and water-resources information for these tributaries, affecting regional water resource management and flood control safety. To address this issue, we selected 20 typical tributaries in the TGR area, among which 18 are ungauged, to build 3D digital river models for these tributaries by self-developed remotely-sensed hydrological station technology along with satellite and unmanned aerial vehicle (UAV) remote-sensing data. Based on this model, we calculated the river discharges, relative water levels, water-surface widths, and other information from January 2016 to July 2023 for the monitoring sections. Results revealed that: 1) The cross-sections of 20 typical tributaries in the TGR area display U-shape, demonstrating mountainous characteristics. The remotely-sensed hydrological station technology demonstrates high accuracy in calculating ungauged tributary discharges in the TGR area, with the average Nash-Sutcliffe efficiency coefficient (NSE) and coefficient of determination (R2) reaching 0.74 and 0.76, respectively. 2) During the study period, the relative water levels of the tributaries changed minimally. The percentages of months with monthly relative water-level fluctuations below 1.2 m in the upper, middle, and lower tributaries of the reservoir were 93.1%, 86.8%, and 87.4% respectively. 3) The average discharges of typical ungauged tributaries were generally stable. However, trend analysis indicated that the discharges of 13 ungauged tributaries have being decreasing, suggesting an overall downward trend in tributary discharges in the reservoir area. 4) The 20 tributaries have abundant annual average and total discharges, with the annual average inflow reaching 16.475 billion m3, accounting for approximately 4.8% of the total annual inflow of the reservoir area, offering substantial water resource support for regional economic development.